Intrapreneurship And Business Perfomance In Supporting Rebranding: A Case Study Of Day With Dya - Ghina Annisa Akyas; Ratih Purbasari; Margo Purnomo (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
A medium-sized business from Bandung, Indonesia, namely Day with Dya brand, which has been operating since 2017, has experienced failure in its business journey and then decided to carry out a gradual rebranding in 2023. This study aims to examine the relationship between intrapreneurship and business performance in supporting the rebranding of Day with Dya. This study uses a qualitative description (QD) method that can discuss the learning journey and descriptions of experiences involving interviews with the owner of Day with Dya named Datu Adrian discussing the case study of Day with Dya rebranding according to intrapreneurial behavior and the impact on the business performance side. Document analysis was also carried out from visual sources, such as photos and videos via Instagram. The results of the study confirmed that the rebranding of the medium-sized business brand Day with Dya was supported by intrapreneurship in running its business, which could improve its brand performance.